Prior host-country work experience and immigrant labor market outcomes: Evidence from Canada - Manish Pandey; James Townsend (IZA Journal of Migration, 2017)
Recent changes to immigration selection policies favor skilled workers with prior work experience in the immigrant host country. Using unique administrative tax data for Canada, we estimate earnings equations to quantify the difference in earnings of immigrants with prior Canadian experience (prefilers) and those without prior experience (non-prefilers). We find that, relative to non-prefilers, entry earnings are higher for prefilers and, for male immigrants, this earnings advantage persists for at least 20 years after arrival. We show that the primary source of the higher entry earnings of prefilers is a higher return to foreign experience. In addition, the prefiler earnings advantage is largest for university graduates and the return to foreign experience is higher for prefilers from Western countries than those from the rest of the world. Our findings suggest that a move towards an immigrant selection system which uses previous host-country work experience as a criterion will improve the labor market performance of immigrants.
Keywords: J61; J31; 330; Immigrant selection; Earnings; Foreign experience returns; Canada